2022
DOI: 10.1111/1365-2664.14271
|View full text |Cite
|
Sign up to set email alerts
|

A monogenean parasite reveals the widespread translocation of the African clawed frog in its native range

Abstract: The management of biological invasions relies upon the development of methods to trace their origin and expansion.Co-introduced parasites, especially monogenean flatworms, are ideal tags for the movement of their invasive hosts due to their short generations, direct life cycles and host specificity. However, they are yet to be applied to trace the intraspecific movement of species in their native ranges. 2.As proof of this concept, we conducted a co-phylogeographic analysis based upon two mitochondrial markers… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 166 publications
0
2
0
Order By: Relevance
“…Given the continuous genetic divergence of the host species reflecting a geographical gradient (De BuSSchere et al 2016;PremachanDra et al 2023), the reported morphological and genetic variation of P. xenopodis most likely represent the extent of the natural diversity as opposed to a complete north-south division (Schoeman et al 2022). This conclusion is supported by the "significant, but continuous" variation in genital spine length that has been observed in P. xenopodis from various host species belonging to Xenopus across Africa in the study by tinSLey & JacKSon (1998b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Given the continuous genetic divergence of the host species reflecting a geographical gradient (De BuSSchere et al 2016;PremachanDra et al 2023), the reported morphological and genetic variation of P. xenopodis most likely represent the extent of the natural diversity as opposed to a complete north-south division (Schoeman et al 2022). This conclusion is supported by the "significant, but continuous" variation in genital spine length that has been observed in P. xenopodis from various host species belonging to Xenopus across Africa in the study by tinSLey & JacKSon (1998b).…”
Section: Discussionmentioning
confidence: 99%
“…The 28S rDNA sequences were uploaded to GenBank and can be found under accession numbers PP263027-PP263032. The 12S rDNA and COX1 sequences, derived from the same polystomatid specimens, were obtained as part of a previous study -available under Genbank accession numbers OP046050-OP046051, OP046054-OP046056, OP046059, OP038566-OP038567, OP038670-OP038572 and OP038575 (Schoeman et al 2022).…”
Section: Molecular and Phylogenetic Analysesmentioning
confidence: 99%